Functional Homology for Antibody-Dependent Phagocytosis Across Humans and Rhesus Macaques - Pollara, Justin; Tay, Matthew Zirui; Edwards, R. Whitney; Goodman, Derrick; Crowley, Andrew R.; Edwards, Robert J.; Easterhoff, David; Conley, Haleigh E.; Hoxie, Taylor; Gurley, Thaddeus; Jones, Caroline; Machiele, Emily; et al. (Frontiers in Immunology, 2021)
Analyses of human clinical HIV-1 vaccine trials and preclinical vaccine studies performed in rhesus macaque (RM) models have identified associations between non-neutralizing Fc Receptor (FcR)-dependent antibody effector functions and reduced risk of infection. Specifically, antibody-dependent phagocytosis (ADP) has emerged as a common correlate of reduced infection risk in multiple RM studies and the human HVTN505 trial. This recurrent finding suggests that antibody responses with the capability to mediate ADP are most likely a desirable component of vaccine responses aimed at protecting against HIV-1 acquisition. As use of RM models is essential for development of the next generation of candidate HIV-1 vaccines, there is a need to determine how effectively ADP activity observed in RMs translates to activity in humans. In this study we compared ADP activity of human and RM monocytes and polymorphonuclear leukocytes (PMN) to bridge this gap in knowledge. We observed considerable variability in the magnitude of monocyte and PMN ADP activity across individual humans and RM that was not dependent on FcR alleles, and only modestly impacted by cell-surface levels of FcRs. Importantly, we found that for both human and RM phagocytes, ADP activity of antibodies targeting the CD4 binding site was greatest when mediated by human IgG3, followed by RM and human IgG1. These results demonstrate that there is functional homology between antibody and FcRs from these two species for ADP. We also used novel RM IgG1 monoclonal antibodies engineered with elongated hinge regions to show that hinge elongation augments RM ADP activity. The RM IgGs with engineered hinge regions can achieve ADP activity comparable to that observed with human IgG3. These novel modified antibodies will have utility in passive immunization studies aimed at defining the role of IgG3 and ADP in protection from virus challenge or control of disease in RM models. Our results contribute to a better translation of human and macaque antibody and FcR biology, and may help to improve testing accuracy and evaluations of future active and passive prevention strategies.